Distributive justice in international environmental policy - theoretical foundation and exemplary formulation - Carsten Helm; Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
Questions of international distributive justice are certainly not new. We need only think of the demand made by the developing countries in the 1970s for a New World Economic Order, which aimed at a more equitable distribution of the benefits derived from the international division of labor. Demands were at that time raised for improved chances for exports to the industrialized countries, stepped-up financial and technology transfers, and a larger share in the decision-making processes in international institutions, above all in the World Bank and the International Monetary Fund. Even though these demands have remained largely unheard, and the debate on a New World Order is as good as over, there are, at the outset of the 21st century, a number of highly topical reasons why the issue of international distributive justice is again attracting more and more attention. Many of these reasons are bound up with the phenomenon of globalization.
Keywords: 300; Internationale Umweltpolitik; Klimaschutz; Luftverunreinigung; Emissionsrechte; Verteilungsgerechtigkeit